Estradiol progesterone ratio on ovulation induction day: a determinant of successful pregnancy outcome after intra cytoplasmic sperm injection - Rehman, Rehana (Iran J Reprod Med, 2014)
Background: Intracytoplasmic sperm injection (ICSI) is an advanced technique employed in assisted reproductive clinics for treatment of infertile couples. The reproductive endocrinologists try their level best to identify factors that enhance success rate after ICSI. Objective: To compare estradiol progesterone ratio on ovulation induction day amongst pregnancy outcome groups following ICSI. Materials and Methods: A cross sectional study was conducted on 323 couples of Assisted Reproductive Clinic in Islamabad from June 2010 till August 2011. Down regulation of females aged 18-40 years with gonadotrophin releasing hormone agonist was followed by calculated stimulation with gonadotrophin injections (COS). Oocytes pickup was done 36 hours after ovulation induction by 16G adapter and double lumen oocyte aspiration needle under general anesthesia. Oocytes were fertilized in vitro, graded and only blastocysts were transferred seven days after ovulation induction. Serum estradiol and progesterone were measured by enzyme linked immuno sorbent assay on ovulation induction day, ratio was compared in three groups of females; no conception with βhCG 5-25 mIU/ml, preclinical abortion with βhCG >25 mIU/ml and no cardiac activity on transvaginal scan and clinical pregnancy with βhCG >25mIU/ml and cardiac activity on transvaginal scan. Results: Females having high estradiol/ progesterone ratio were able to achieve clinical pregnancy shown by a positive βhCG and cardiac activity on transvaginal scan. These females also had significantly high number of oocytes, endometrial thickness and implantation rate. Conclusion: A high estradiol/progesterone ratio on the day of ovulation induction predicts the success of intra cytoplasmic sperm injection.